2017
DOI: 10.1002/adsu.201600020
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Material Properties and Pyroelectric‐Generating Performance of PZTs

Abstract: according to a given temperature variation during generating cycle:It was indicated that the D F could be effective as a FOM for the pyroelectric generating performance and the dielectric loss (tanδ) significantly affected the generating performance in addition to p under hightemperature and electric-field conditions. Furthermore, of the PZTs tested, the C-91 sample (see further), which showed the highest generating performance, resulted in a generated energy of 1.3 mW cm −3 in the engine dynamometer assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
1
17
1
Order By: Relevance
“…[26] Many attempts have been made to utilize PE based on the Olsen cycle in terms of theoretical investigations, materials, and systems. [41] They considered FOMs with temperature changes in the high-temperature regime, and the modified FOMs corresponded well with the experimental results. [36] This cycle consisted of four steps with temperature changes and electric field changes, which were not isothermal and isoelectric.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…[26] Many attempts have been made to utilize PE based on the Olsen cycle in terms of theoretical investigations, materials, and systems. [41] They considered FOMs with temperature changes in the high-temperature regime, and the modified FOMs corresponded well with the experimental results. [36] This cycle consisted of four steps with temperature changes and electric field changes, which were not isothermal and isoelectric.…”
Section: Introductionsupporting
confidence: 53%
“…[45,46] The result of the assessments with PMN-PT is displayed with the previous results of PZT (A) [36] and soft PZT (B) [41] in Figure 8. [45,46] The result of the assessments with PMN-PT is displayed with the previous results of PZT (A) [36] and soft PZT (B) [41] in Figure 8.…”
Section: Generating Assessment With a Real Engine Dynamometermentioning
confidence: 53%
See 2 more Smart Citations
“…6(d) presents the results of the assessments over the total drive cycle with PNZST samples compared to previous results. 1,9 The net mean power was 40.8 mW cm À3 (accumulated generating energy of 49 117.4 J L À1 ), which is the highest value produced by any material in our energy harvesting system to date 1,[9][10][11][12] and is 314 times greater than what we presented in our rst report. 1 The comparisons of the current maximum power and energy density for pyroelectric energy harvesting studies for various materials are shown in Table 2, together with the respective operating conditions.…”
Section: Novel Electro-thermodynamic Cyclementioning
confidence: 52%